2022
DOI: 10.1002/dev.22337
|View full text |Cite
|
Sign up to set email alerts
|

“Katerina gets mad”: Infants’ physiological and behavioral responses to co‐viewing educational, self‐regulatory media

Abstract: A growing body of research has focused on the physiological impact of media on older children and adolescents. Less research has been focused on the potential physiological impact of media on infants and younger children, especially media designed to be age appropriate and educational in content. In this study, we examined respiratory sinus arrhythmia (RSA) in infants (N = 269, M age = 17.13 months) while they co-viewed an educational video clip that modeled emotion regulation and contrasted their physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 112 publications
(169 reference statements)
0
7
0
1
Order By: Relevance
“…In contrast, research shows that vagal activation (RSA increase) or a flattened RSA response in the face of social challenges may reflect poorer adaptation to stress (e.g., Wagner et al, 2023) such has been observed in the face of frequent exposure to interparental conflict (e.g., El-Sheikh et al, 2001;Katz & Gottman, 1995) or children exhibiting ambivalent attachment (Paret et al, 2015). By comparison, vagal activation (RSA increase) in the face of nonthreatening social stimuli, such as when children are watching a calming video vignette, is believed to be indicative of increased attention and physiological regulation (Porter, Stockdale, et al, 2022;Wagner et al, 2023) At the same time, we recognize that some toddlers may demonstrate a contrasting pattern of physiological response to parents mobile device distraction, experiencing vagal activation (RSA increase) rather than vagal withdrawal. We suspect that children exposed more frequently to parents' technoference may develop less adaptive physiological responses to parents' cell phone distractions.…”
Section: Polyvagal Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, research shows that vagal activation (RSA increase) or a flattened RSA response in the face of social challenges may reflect poorer adaptation to stress (e.g., Wagner et al, 2023) such has been observed in the face of frequent exposure to interparental conflict (e.g., El-Sheikh et al, 2001;Katz & Gottman, 1995) or children exhibiting ambivalent attachment (Paret et al, 2015). By comparison, vagal activation (RSA increase) in the face of nonthreatening social stimuli, such as when children are watching a calming video vignette, is believed to be indicative of increased attention and physiological regulation (Porter, Stockdale, et al, 2022;Wagner et al, 2023) At the same time, we recognize that some toddlers may demonstrate a contrasting pattern of physiological response to parents mobile device distraction, experiencing vagal activation (RSA increase) rather than vagal withdrawal. We suspect that children exposed more frequently to parents' technoference may develop less adaptive physiological responses to parents' cell phone distractions.…”
Section: Polyvagal Theorymentioning
confidence: 99%
“…When the vagal brake is engaged, parasympathetic inputs increase, causing HR to slow while simultaneously increasing HR variability (HRV). This response is believed to undergird regulatory processes that support dynamic social interactions (Porges & Furman, 2011; Porter, Yang, et al., 2022). However, when the vagal brake is released, parasympathetic influences are removed, and sympathetic responses are activated that causes HR to accelerate while simultaneously causing HRV to decrease to help prepare the body to respond to environmental challenges (Porges, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karena dampaknya terhadap peningkatan perilaku dan status kesehatan gigi dan mulut pada anak (Maulanti & Nurmala, 2021), tidak hanya itu saja ternyata media pendidikan juga dapat meningkatkan pengetahuan dan pemahaman masyarakat terhadap kasus-kasus yang sering muncul di masyarakat sebagai suatu permasalahan seperti gizi, imunisasi dan pneumonia (Solikhah et al, 2021). Adapun topik yang menarik untuk dibahas saat ini adalah berkaitan dengan media Pendidikan yang diberikan pada anak-anak harus sesuai dengan respon fisiologis anak (Porter et al, 2022) bisa kita lihat dari kecendrungan orang tua yang menggunakan tablet untuk membantu anak tidur. Topik selanjutnya yang menarik untuk dibahas pentingnya penerapan strategi komunikasi terutama melalui semua media, bertujuan untuk memantapkan kesadaran dan perilaku lingkungan warga negara sebagai kepentingan global (Rojas et al, 2022) serta media merupakan basis model komunikatif praktik pendidikan saat ini (Kotlyar et al, 2022) .…”
Section: Analisis Kata Kunciunclassified